STRATEGY OF HOUSEHOLD FISHERMEN IN THE FACE OF POVERTY IN DESA KOTA PARI OF PANTAI CERMIN SUB-DISTRICT OF SERDANG BEDAGAI REGENCY OF NORTH SUMATERA PROVINCE - Agustina Saragih; Darwis Darwis; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted on March 2018 held at Desa Kota Pari of PantaiCerminSub-district PantaiCermin Serdang Bedagai Regency of North Sumatera Province. This study aims to identify the factors causing poverty in the Desa Kota Pari and to formulate what strategies are carried out by fishermen in the face of poverty. The method used in this research is survey method with 41 households as respondents, the determination of respondents through simple random sampling. Factors causing poverty in the Desa Kota Pari is influenced by the low human resources which is characterized by the low level of education of fishermen, other causes of poverty are fluctuations in fish season, simple catching tools, consumptive behavior and income level and household expenditure. The strategy of dealing with the most powerful poverty to increase household income is to optimize the role of family members, other than that the strategy undertaken by the fishermen in the form of diversification of work, and borrowing. Keywords:Strategy,Household, Poverty, Fisherman